Desch‐Schappacher perturbation of one‐parameter semigroups on locally convex spaces. Issue 8 (3rd February 2015) - Jacob, Birgit; Wegner, Sven‐Ake; Wintermayr, Jens
Abstract : We prove a Desch‐Schappacher type perturbation theorem for strongly continuous and locally equicontinuous one‐parameter semigroups which are defined on a sequentially complete locally convex space.